ANALISIS STRUKTUR EKSPERIENSIAL PADA TERJEMAHAN UNSUR POST-MODIFIER DALAM KELOMPOK NOMINA DAN DAMPAKNYA TERHADAP KUALITAS TERJEMAHAN DALAM BUKU TO BEE OR NOT TO BEE KARYA JOHN PENBERTHY - Yulita Rusli Rahmawati (Universitas Sebelas Maret, 2018)
This research aims to determine the forms of post-modifier on nominal group, the use of translation technique, and the impact of the translation technique to the translation quality in the book To Bee or Not to Bee. The elements have their roles and functions experientially. In order to get the aspect of readability of the nominal group, the translator must have understanding of how the nominal group is formed based on the experiential structure. This research uses descriptive and qualitative based on Systemic Functional Linguistics Approach. The data collecting techniques used in this research are criterion- based sampling and document analysis by using document analysis, questionnaire and interview in order to obtain the data by giving some questions to the informants. The results of this research show that there are 536 used in this research which consist of non-finite clauses such as relative clauses, participle clauses (past and present) and to-infinitive. The results show there are 124 data (59,61 %) unchanged, 78 data (37,50%) shifting and 6 data (2,89 %) untranslated. Adjective phrases consist of 54 data (10,08 %) with 39 data (72,22 %) unchanged, 14 data (25,93 %) shifting and 1 data (1,85 %) untranslated. Preposition phrases consist of 274 data (51,11 %) with 143 data (52,19 %) unchanged, 97 data (35,41 %) shifting and 34 data (12,40 %) untranslated. The applications of the translation techniques used in this research are single techniques, double techniques, and triple techniques. They have impacts to the translation quality especially in the forms of post-modifier in the nominal groups.